The Oxford handbook of political economy - Weingast, Barry R.; Wittman, Donald A. (Oxford : Oxford University Press, 2008)
Over its lifetime, 'political economy' has had different meanings. This handbook views political economy as a synthesis of the various strands of social science, treating it as the methodology of economics applied to the analysis of political behaviour and institutions.
The reach of political economy / Barry R. Weingast & Donald A. Whitman. Voters, candidates, and parties / Stephen Ansolabehere. Rational voters and political advertising / Andrea Prat. Candidate objectives and electoral equilibrium / John Duggan. Political income redistribution / John Londregan. The impact of electoral laws on political parties / Bernard Grofman. Legislatures and parliaments in comparative context / Michael Laver. The organization of democratic legislatures / Gary W. Cox. Coalition government / Daniel Diermeier. Does bicameralism matter? / Michael Cutrone, Nolan McCarty. The new separation-of-powers approach to American politics / Rui J.P. de Figueiredo, Jr., Tonja Jacobi, Barry R. Weingast. Pivots / Keith Krehbiel. The political economy of the US presidency / Charles M. Cameron. Politics, delegation, and bureaucracy / John D. Huber, Charles R. Shipan The judiciary and the role of law / Mathew D. McCubbins, Daniel B. Rodriguez. Constitutionalism / Russell Hardin. Self-enforcing democracy / Adam Przeworski. Constitutions as expressive documents / Geoffrey Brennan, Alan Hamlin. The protection of liberty, property, and equality / Richard A. Epstein. Federalism / Jonathan A. Rodden. Social choice / Herve Moulin. A tool kit for voting theory / Donald G. Saari. Interpersonal comparisons of well-being / Charles Blackorby, Walter Bossert. Fair division / Steven J. Brams. Structure and coherence in the political economy of public finance / Stanley l. Winer, Walter Hettich. Political economy of fiscal good mechanism / John Ledyard. Fiscal competition / David E. Wildasin. The non-politics of monetary policy / Susanne Lohmann. Political-economic cycles / Robert J. Franzese, Jr. and Karen Long Jusko. Voting and the macroeconomy / Douglas A. Hibbs, Jr. The political economy of exchange rates / J. Lawrence Broz, Jeffry A. Freiden. Capitalism and democracy / Torben Iversen. Inequality / Edward l. Glaeser. Comparative perspectives on the role of the state in the economy / Anne Wren. Democratization : post-communist implications / Anna Grzymala-Busse, Pauline Jones Luong. Paths of economic and political development / Daron Acemoglu, James A. Robinson. Authoritarian government / Stephen Haber. The role of the state in development / Robert H. Bates. Electoral systems and economic policy / Torsten Persson, Guido Tabellini. Economics geography / Antony J. Venables. international political economy : a maturing interdiscipline / David A. Lake. National borders and the size of nations / Enrico Spolaore. European integration / Barry Eichengreen. Trade, immigration, and cross-border investment / Ronald Rogowski. Central issues in the study of international conflict / Bruce Bueno de Mesquita. Ethnic mobilization and ethnic violence / James D. Fearon. Democracy, peace, and war / Dan Reiter, Allan C. Stam. Anarchy / Stergios Skaperdas. Economic methods in positive political theory / David Austen-Smith. Laboratory experiments / Thomas R. Palfrey. The tool kit of economic sociology / Richard Sweberg. The evolutionary basis of collective action / Samuel Bowles, Herbert Gintis. Question about a paradox / Kenneth J. Arrow. Politics and scientific enquiry : retrospective on a half-century / James M. Buchanan. The future of analytical politics / Melvin J. Hinich. What is missing from political economy / Douglass C. North. Modeling party competition in general elections / John E. Roemer. Old questions and new answers about institutions : the Riker objection revisited / Kenneth A. Shepsle.
Originally published: 2006.
Includes bibliographical references and index.
Texto en inglés.
Description based on print version record.
Keywords: Economics -- Handbooks, manuals, etc; Political science -- Handbooks, manuals, etc; Politics, Practical -- Handbooks, manuals, etc